Novel technologies in food science : their impact on products, consumer trends and the environment - McElhatton, Anna; Sobral, Paulo José do Amaral (Integrating food science and engineering knowledge into the food chain, 2012)
Covers novel technologies, including high pressure, antimicrobials, and electromagnetism, and their impact